Influence of bismuth substitution on structural and optical properties of CuFe2-xBixO4 spinel structure - Hamid Hamrah; Ahmad Gholizadeh (Progress in Physics of Applied Materials)
CuFe2-xBixO4 (x=0.0-2.0) spinel structures were synthesized using a sol-gel auto-combustion method. The effects of Bi3+ substitution on structural and optical properties were investigated using X-ray diffraction, Fourier-transformed infrared spectroscopy, and UV-vis spectroscopy. A phase transition was observed in CuFe2-xBixO4 with increasing Bi content, leading to enhanced lattice parameters a and c due to Bi3+ larger ionic radius. Crystallite size decreased as Bi substitution increased, attributed to the reduced mobility and higher mass of Bi3+ ions. The tunability of structural and optical properties was achieved through controlled Bi substitution, with optical band gap energy increasing due to local distortions from Bi3+ ions in the CuFe2O4 lattice. CuFe2-xBixO4spinel structures show promise for applications in photocatalysis, gas sensors, pigments, and magnetic materials. We will clearly outline the existing knowledge in the field of Bi3+-substituted copper ferrite nanoparticles, focusing on the need for a comprehensive understanding of the structural and optical property changes resulting from Bi3+ substitution.